Selective inhibition of prostaglandin D2 biosynthesis in human mast cells to overcome need for multiple receptor antagonists: Biochemical consequences. Issue 4 (12th February 2021) - Johnsson, Anna‐Karin; Choi, Jeong‐Hee; Rönnberg, Elin; Fuchs, David; Kolmert, Johan; Hamberg, Mats; Dahlén, Barbro; Wheelock, Craig E.; Dahlén, Sven‐Erik; Nilsson, Gunnar
Abstract: Background: The major mast cell prostanoid PGD2 is targeted for therapy of asthma and other diseases, because the biological actions include bronchoconstriction, vasodilation and regulation of immune cells mediated by three different receptors. It is not known if the alternative to selectively inhibit the biosynthesis of PGD2 affects release of other prostanoids in human mast cells. Objectives: To determine the biochemical consequences of inhibition of the hematopoietic prostaglandin D synthase (hPGDS) PGD2 in human mast cells. Methods: Four human mast cell models, LAD2, cord blood derived mast cells (CBMC), peripheral blood derived mast cells (PBMC) and human lung mast cells (HLMC), were activated by anti‐IgE or ionophore A23187. Prostanoids were measured by UPLC‐MS/MS. Results: All mast cells almost exclusively released PGD2 when activated by anti‐IgE or A23187. The biosynthesis was in all four cell types entirely initiated by COX‐1. When pharmacologic inhibition of hPGDS abolished formation of PGD2, PGE2 was detected and release of TXA2 increased. Conversely, when the thromboxane synthase was inhibited, levels of PGD2 increased. Adding exogenous PGH2 confirmed predominant conversion to PGD2 under control conditions, and increased levels of TXB2 and PGE2 when hPGDS was inhibited. However, PGE2 was formed by non‐enzymatic degradation. Conclusions: Inhibition of hPGDS effectively blocks mast cell dependent PGD2 formation. The inhibition was associated with redirected use of the intermediate PGH2 and shunting into biosynthesis of TXA2 . However, the levels of TXA2 did not reach those of PGD2 in naïve cells. It remains to determine if this diversion occurs in vivo and has clinical relevance.